2022
DOI: 10.48550/arxiv.2204.06608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modularity benefits reinforcement learning agents with competing homeostatic drives

Abstract: The problem of balancing conflicting needs is fundamental to intelligence. Standard reinforcement learning algorithms maximize a scalar reward, which requires combining different objective-specific rewards into a single number. Alternatively, different objectives could also be combined at the level of action value, such that specialist modules responsible for different objectives submit different action suggestions to a decision process, each based on rewards that are independent of one another. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…There is also growing evidence that dopamine neurons are sensitive to various aspects of the state-space such as locomotion and kinematic behaviour (Barter et al, 2015;Dodson et al, 2016;Engelhard et al, 2019;Kremer, Flakowski, Rohner, & Lüscher, 2020) as well as choice behaviour (Coddington & Dudman, 2018;Parker et al, 2016) and indeed that this heterogeneity is topographically organized due to spatially organized cortical projections (Engelhard et al, 2019;Howe & Dombeck, 2016). Additionally, recent theoretic work has demonstrated that RL agents including separate modules predicting reward in different dimensions have advantages in task requiring acquisition of multiple resource types (Dulberg, Dubey, Berwian, & Cohen, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There is also growing evidence that dopamine neurons are sensitive to various aspects of the state-space such as locomotion and kinematic behaviour (Barter et al, 2015;Dodson et al, 2016;Engelhard et al, 2019;Kremer, Flakowski, Rohner, & Lüscher, 2020) as well as choice behaviour (Coddington & Dudman, 2018;Parker et al, 2016) and indeed that this heterogeneity is topographically organized due to spatially organized cortical projections (Engelhard et al, 2019;Howe & Dombeck, 2016). Additionally, recent theoretic work has demonstrated that RL agents including separate modules predicting reward in different dimensions have advantages in task requiring acquisition of multiple resource types (Dulberg, Dubey, Berwian, & Cohen, 2022).…”
Section: Discussionmentioning
confidence: 99%